Geo-Congress 2024: Foundations, Retaining Structures, Geosynthetics, and Underground Engineering - Evans, T. Matthew; Stark, Nina; Chang, Susan (American Society of Civil Engineers, 2024)
GSP 350 contains 53 peer-reviewed papers on foundations, retaining structures, geosynthetics, and underground engineering presented at Geo-Congress 2024, held in Vancouver, British Columbia, Canada, February 25-28, 2024.